A New Family of Trinuclear Nickel(II) Complexes as Single‐Molecule Magnets. Issue 12 (30th January 2013) - Biswas, Rituparna; Ida, Yumi; Baker, Michael L.; Biswas, Saptarshi; Kar, Paramita; Nojiri, Hiroyuki; Ishida, Takayuki; Ghosh, Ashutosh
Abstract Three new trinuclear nickel (II) complexes with the general composition [Ni3L3(OH)(X)](ClO4) have been prepared in which X=Cl− (1), OCN− (2), or N3− (3) and HL is the tridentate N, N, O donor Schiff base ligand 2‐[(3‐dimethylaminopropylimino)methyl]phenol. Single‐crystal structural analyses revealed that all three complexes have a similar Ni3 core motif with three different types of bridging, namely phenoxido (μ2 and μ3), hydroxido (μ3), and μ2‐Cl (1), μ1, 1‐NCO (2), or μ1, 1‐N3 (3). The nickel(II) ions adopt a compressed octahedron geometry. Single‐crystal magnetization measurements on complex 1 revealed that the pseudo‐three‐fold axis of Ni3 corresponds to a magnetic easy axis, being consistent with the magnetic anisotropy expected from the coordination structure of each nickel ion. Temperature‐dependent magnetic measurements indicated ferromagnetic coupling leading to an S=3 ground state with 2J/k=17, 17, and 28 K for 1, 2, and 3, respectively, with the nickel atoms in an approximate equilateral triangle. The high‐frequency EPR spectra in combination with spin Hamiltonian simulations that include zero‐field splitting parameters DNi/k=−5, −4, and −4 K for 1, 2, and 3, respectively, reproduced the EPR spectra well after a anisotropic exchange term was introduced. Anisotropic exchange was identified as Di, j/k=−0.9, −0.8, and −0.8 K for 1, 2, and 3, respectively, whereas no evidence of single‐ion rhombic anisotropy was observed spectroscopically. Slow relaxation of the magnetization at low temperatures is evident from the frequency‐dependence of the out‐of‐phase ac susceptibilities. Pulsed‐field magnetization recorded at 0.5 K shows clear steps in the hysteresis loop at 0.5–1 T, which has been assigned to quantum tunneling, and is characteristic of single‐molecule magnets.